IMPLEMENTATION OF POLICIES FOR MICIMPLEMENTATION OF POLICIES FOR MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) DEVELOPMENT IN INCREASING BUSINESS COMPETITIVENESS (Study in Micro, Small and Medium Enterprises in Kendari City) - Husriadi, Adi; Yulianto, Edy; Mawardi, Kholid (The International Journal of Accounting and Business Society, 2020)
ABSTRACTPurpose — This research aims to find out and explain the implementation of policies for the development of micro, small and medium enterprises (MSMEs) in improving business competitiveness in Kendari City and to describe the effectiveness of the policies for developing micro, small and medium enterprises (MSMEs) in increasing business competitiveness.Design/methodology/approach — This research uses a narrative qualitative approach. Data collection techniques used are interviews, in-depth observation, and Snowball sampling.Findings — The results of the research found that the implementation of policies realized through training programs in the effort to develop micro, small and medium enterprises (MSMEs) to have competitiveness was not maximized due to the lack of follow-up (evaluation) of the programs that had been implemented, the existence of MSMEs that have not gained understanding after participating in training such as financial report management, inadequate human resources (HR), no special expertise to conduct financial management assistance, and the absence of product service center.Practical Implications —  The effectiveness of the policies will determine the improvement of business competitiveness for micro, small and medium enterprises (MSMEs). Originality/value — This research presents the case of the implementation of policies for the development of micro, small, and medium enterprises (MSMEs) in Kendari City, which might impact the improvement of the workers’ business competitiveness.Keywords Policies, MSMEs, Competitiveness.Paper Type research paper (case study)